(untitled) (Research, Society and Development, 2020)
Regular physical activity is essential to prevent and assist in the treatment of chronic non-communicable diseases, pointed out by the WHO as being responsible for 71% of all deaths in the world, including 15 million deaths per year aged 30 and 70 years. The regular practice of physical activities with moderate intensity can be considered an ally in increasing immunity and concatenated with cognitive and behavioral techniques that promote health, quality of life and develop human potential. In order to present the benefits of physical activity associated with a technique recognized worldwide, functional neurometry will be presented through a descriptive analysis with emphasis on its training protocols and benefits for physical and emotional health. The training has specific purposes, which in general make it possible to adapt the nervous system in the face of stressful situations, by stabilizing the physical, mental and nutritional condition that associated with physical activity can enhance the balance of the Autonomic Nervous System, which has great influence on the emotional and physiological aspects.